PENGARUH PROFESIONALISME, INDEPENDENSI, KOMPETENSI, DAN INTEGRITAS AUDITOR INTERNAL TERHADAP KUALITAS AUDIT - Pratiwi, Ni Putu Putri; Yenni Latrini, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Failure of internal auditors causes low quality of financial reports. The low quality of financial statements affects the perception of users of financial statements on audit quality. This study aims to determine the effect of professionalism, independence, competence and integrity of internal auditors on audit quality at BPR Gianyar Regency, using an associative quantitative approach. This research was conducted at 24 BPR in Gianyar Regency. The research sample was 24 respondents, using the saturated sample method (census). Collecting data using a survey method with a questionnaire. The analysis technique used is multiple regression analysis. The results showed that the variables of professionalism, independence, competence, and the integrity of the internal auditor has a positive effect on audit quality at BPR Gianyar Regency.